Whole genome re-sequencing in 437 tobacco germplasms identifies plant height candidate genes - Yanru Song; Yuanheng Wang; Ying Liu; Haozhen Li; Jie Ding; Xingfu Wu; Yongping Li; Fangchan Jiao; Long Yang (Scientific Reports)
Abstract Tobacco is one of the most important model plants. Plant height is one of the most important agronomic traits in tobacco. To better understand the population genetic structure and the genetic basis of plant height in tobacco, 437 tobacco germplasms were whole genome re-sequencing in this study. A total of 2,263,775 high-quality single nucleotide polymorphisms were identified. The analysis of the population genetic structure showed that tobacco germplasm could be divided into 8 clusters. In addition, gene flow was found between flue-cured tobacco and ustic tobacco, as well as between oriental tobacco and air-cured tobacco. Three genes associated with plant height were identified as candidate genes by genome-wide association study. This study provides valuable genetic resources for population structure analysis and elucidation of the genetic basis of various traits. It helps to improve the efficiency of molecular breeding.